Harnessing OSINT to enhance the investigation of economic crimes - Adionyi, Claire (Journal of Anti-Corruption Law, 2024)
Economic crimes are considered one of the fastest-growing global threats. As noted by UNODC, this threat is increasingly enabled by technological advancements such as electronic banking and expanded internet access. While these advancements facilitate economic crimes, this paper argues that they also provide new avenues for economic crime investigators to harness the power of open-source intelligence (OSINT). Defined as publicly available information that is accessible to any member of the public without the need for special legal status or authorisation, OSINT offers a wealth of untapped evidence that can enhance traditional investigative methods significantly. This paper explores how OSINT, defined as methods of gathering and analysing open-source information can be leveraged to supplement and transform traditional approaches to economic crime investigations. By relying on the hypothesis that OSINT can significantly augment the range and accessibility of available evidence, this research proposes that the integration of OSINT into conventional investigation techniques will result in a more efficient and comprehensive economic crime investigation. Based on a desk study of both primary and secondary data, this paper aims to demonstrate how OSINT tools and strategies can provide innovative solutions to bolster the ongoing fight against economic crimes.